Tobacco cessation: what role can dental professionals play? - Abhishek Mehta; Gurkiran Kaur (Revista Sul-Brasileira de Odontologia, 2013)
Tobacco dependence is classified as a disease by the International Classification of Diseases (ICD-10), but, medical and dental professionals have neither seriously taken this fact nor made any serious attempt to tackle this disease. Apart from supporting wider tobacco control measures, oral health professionals can help patients to stop using tobacco. This may be the single most important service dentists can provide for their patients’ overall health. Objective: This review is prepared with the object to help both clinicians and oral health professionals to scale up their involvement in tobacco control activities, including advocacy and smoking cessation programs. Literature review: Studies have shown that smokers indicate that they want to quit, but a meagre 2% succeed. The dental practice setting provides a unique opportunity to assist tobacco users in achieving tobacco abstinence. Still, More than 40% of dentists do not routinely ask about tobacco use and 60% do not routinely advise tobacco users to quit, while 61.5% of dentists believe their patients do not expect tobacco cessation services. Conclusion: Interventions by dentist has been found to be effective in helping people to quit tobacco consumption. A step-wise approach and patience must be adopted while dealing with such patients.